Incidence and location of residual gaps identified by a high-density grid-style catheter after PVI is confirmed by pacing the ablation lines. (24th May 2021) - Giuggia, M; Volpicelli, M; Mantica, M; Notarangelo, MF; Sundaram, S; Gora, P; Bottoni, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The continual pursuit of more durable pulmonary vein isolation (PVI) has led ablationists to evaluate many different techniques for confirming isolation. One such technique involves using the ablation catheter to pace along the ablation lines, ensuring loss of pace capture. Initial observations from a small cohort of patients suggested that a high-density, grid style mapping catheter (HD Grid) enabling simultaneous recording of adjacent bipolar EGMs in two directions (HD Wave) may identify residual gaps that are missed when using the technique of pacing the ablation line in isolation. The true incidence of these residual gaps as identified in a large patient population has not been previously reported. Purpose: To quantify in a large cohort of AF ablation patients, the presence of residual gaps identified by HD Grid which are missed by a technique of pacing along the ablation lines with the ablation catheter. Methods: Self-reported data was prospectively collected in AF radiofrequency ablation procedures in which PVI was first confirmed by pacing along the ablation line followed by assessment using the HD Grid. Procedural characteristics and acute outcomes, including the incidence and location of gaps post-ablation, were analyzed. Results: Data was collected in 111 AF ablation procedures performed in 18 centers across the United States and Europe. Paroxysmal (PAF), persistent (PersAF), and longstanding persistent AF (LsPersAF) accounted for 60.4%, 33.3%, and 6.3% of cases, respectively. Overall, 64.0% of ablations were de novo procedures. Following ablation, PVI was confirmed in all cases by pacing the ablation line with an average output of 9.1 ± 2.6mA and pulse width of 2.1 ± 0.5ms. Adenosine was administered in 3.6% of cases, isoproterenol in 3.6%, and a combination in 0.9%. PVI was then reassessed with HD Grid using a variety of techniques including exit block (91.0%), voltage mapping (82.0%), loss of pace capture along the ablation lines (47.7%), and entrance block (27.0%); note: total exceeds 100% as more than one technique may be used in a single case. A second dose of adenosine was administered in 2.7% of cases; isoproterenol in 2.7%. The HD Wave configuration was used in 96.4% of cases. HD Grid identified a total of 130 gaps in 65 (58.6%) patients, which were missed by pacing the ablation line (Figure 1). Conclusions: In over half of the patients evaluated, the HD Grid identified residual PVI gaps that were missed when isolation was confirmed by using the ablation catheter to pace the ablation lines. These results suggest that the pacing technique, used in isolation, is not sufficient for complete gap detection. One limitation of this analysis was the use of a workflow which consistently assessed PVI with the HD Grid following confirmation of isolation by pacing the ablation lines. Despite this limitation, the rate at which residual gaps were identified is noteworthy and likely warrants additional study.